Reverse transcriptase encoded by a retrotransposon from the trypanosomatid Crithidia fasciculata. - Gabriel, A (1991)
The long interspersed nuclear element (LINE)-like elements are a distinct family of eukaryotic transposons that contain a long open reading frame with limited sequence homology to retroviral reverse transcriptases. Unlike many retrotransposons, they lack long terminal repeats. The mechanism by which LINE-like elements move within the genomes of their hosts remains speculative. We have used an unusual approach to express and detect enzymatic activities associated with Crithidia retrotransposable element 1 (CRE1), a site-specific LINE-like element found in the insect trypanosomatid Crithidia fasciculata. A chimeric gene fusing the yeast retrotransposon Ty1 and the CRE1 open reading frame is constructed and then overexpressed in yeast. Fusion proteins are packaged into virus-like particles, which can be partially purified and directly analyzed for enzymatic activity. Here we demonstrate that CRE1 encodes an RNA-directed DNA polymerase. These data provide direct biochemical evidence that this widely distributed class of retrotransposons encodes reverse transcriptase and sets the stage for a detailed understanding of the mechanisms involved in LINE-like element transposition.